Aldoxime dehydratase: probing the heme environment involved in the synthesis of the carbon-nitrogen triple bond - Pinakoulaki, Eftychia; Pavlou, Andrea; Koutsoupakis, Constantinos; Sawai, Hitomi; Kato, Yasuo; Asano, Yasuhisa; Aono, Shigetoshi (My University, 2011)
Fourier transform infrared (FTIR) spectra, "light" minus "dark" difference FTIR spectra, and time-resolved step-scan (TRS 2) FTIR spectra are reported for carbonmonoxy aldoxime dehydratase. Two C-O modes of heme at 1945 and 1964 cm -1 have been identified and remained unchanged in H 2O/D 2O exchange and in the pH 5.6-8.5 range, suggesting the presence of two conformations at the active site. The observed C-O frequencies are 5 and 16 cm -1 lower and higher, respectively, than that obtained previously (Oinuma, K.-I.; et al. FEBS Lett.2004, 568, 44-48). We suggest that the strength of the Fe-His bond and the neutralization of the negatively charged propionate groups modulate the ν(Fe-CO)/ν(CO) back-bonding correlation. The "light" minus "dark" difference FTIR spectra indicate that the heme propionates are in both the protonated and deprotonated forms, and the photolyzed CO becomes trapped within a ligand docking site (ν(CO) = 2138 cm -1). The TRS 2-FTIR spectra show that the rate of recombination of CO to the heme is k 1945 cm -1 = 126 ± 20 s -1 and k 1964 cm -1 = 122 ± 20 s -1 at pH 5.6, and k 1945 cm -1 = 148 ± 30 s -1 and k 1964 cm -1 = 158 ± 32 s -1 at pH 8.5. The rate of decay of the heme propionate vibrations is on a time scale coincident with the rate of rebinding, suggesting that there is a coupling between ligation dynamics in the distal heme environment and the environment sensed by the heme propionates. The implications of these results with respect to the proximal His-Fe heme environment including the propionates and the positively charged or proton-donating residues in the distal pocket which are crucial for the synthesis of nitriles are discussed.
Keywords: Cyanides; Nitriles; Hydratase NHase